PROBLEMS AND SOLUTIONS TO IMPROVE BANKING PERFORMANCE: IN THE PANDEMIC SITUATION OF COVID-19 IN INDONESIA - Rudi Triadi Yuliarto (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2021)
This study aims to find out the main problems faced by the banking industry in Indonesia and what solutions are appropriate to overcome them, in the COVID-19 pandemic situation in Indonesia. Using a descriptive method with secondary data which aims to provide data and fact support from the analysis and observation process carried out. The results of the study concluded that there were three main problems, namely liquidity, bad credit, and loss of intermediary income. Liquidity problems are resolved by lending liquidity funds, loosening liquidity, and incentivizing interest rates. The problem of bad credit is resolved by relaxing payment delays in the form of loan restructuring of up to 12 months. The problem of intermediary income is overcome by providing digital financial service innovations that can provide speed and ease of banking access without having to physically meet.